2015
DOI: 10.7439/ijbar.v6i1.1565
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Performance of Date Palm Pollen on Urea and Creatinine Levels in Adult Female Rats Exposed to Lead Acetate Intoxication

Abstract: Background and objective: Exposure to lead continues to a serious public problem. The objective is to elucidate the effect of lead acetate exposure on serum Concentration of urea and creatinine in adult female rats. Methods:Forty-eight adults female rats divided in to four groups (12 rats/group) .Group 1, (T1), given date palm pollen (150 mg/kg. B.W.) Group 2,(T2) given lead acetate (10mg/kg. B.W.), group 3, (T3) given lead acetate (10mg/kg. B.W.) and date palm pollen (150 mg/kg. B.W) for 6 weeks, Group 4(Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…This is line with the report of Iteire et al [13] that revealed mild vessel congestion in the liver of rats treated with a high dose of the extract. The observed improved kidney function in rats is attributed to the antioxidant and free radical scavenging properties of PD, which was previously observed in the liver of rats by Al Qarawi et al [14] and Mohamed et al [15,16] It was as also observed by Salim [6] that PD has the ability to counteract the toxic effect of lead acetate associated with improved renal histology and serum concentration of urea and creatinine and as observed by Saafi-Ben et al [7,17], date palm fruit extract significantly reduced lipid peroxidation and restored antioxidant defense enzymes and improved histopathologic changes in kidneys of rats.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This is line with the report of Iteire et al [13] that revealed mild vessel congestion in the liver of rats treated with a high dose of the extract. The observed improved kidney function in rats is attributed to the antioxidant and free radical scavenging properties of PD, which was previously observed in the liver of rats by Al Qarawi et al [14] and Mohamed et al [15,16] It was as also observed by Salim [6] that PD has the ability to counteract the toxic effect of lead acetate associated with improved renal histology and serum concentration of urea and creatinine and as observed by Saafi-Ben et al [7,17], date palm fruit extract significantly reduced lipid peroxidation and restored antioxidant defense enzymes and improved histopathologic changes in kidneys of rats.…”
Section: Discussionsupporting
confidence: 72%
“…Another report by Arshad et al [4] also stated that it had anticancer activities, while the anti-diarrheal activity was demonstrated by Abdulla and Al-Taher [5]. More recently, Salim [6] observed that date palm pollen has the ability to counteract the toxic effects of lead acetate with improved renal histological features, as well as a serum concentration of urea and creatinine. Saafi-Ben et al [7] reported that date palm fruit extract significantly reduced lipid peroxidation and restored antioxidant defense enzymes in the kidney and improved the histopathology changes in the kidney of rats, in which oxidative stress and nephrotoxicity were induced by dimethoate.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al (2020b) reported that exposure of ammonium to chickens at higher concentrations caused a signi cant (P < 0.05) down-regulation in the level of antioxidant enzyme activities such as CAT, GSH-Px, and SOD. The supplementation lead acetate indicated a considerable (p<0.05) rise in creatinine and urea with regarding the untreated group (Salim et al 2015). Elevation in the creatinine level in conducted research is in favor of the results stated by Obi-Ezeani et al (2020).…”
Section: Discussionmentioning
confidence: 67%
“…Literature data on the effects of acute Pb exposure triggering oxidative stress in the kidney of animals are rare. The administration of lead acetate showed a significant (p<0.05) increase in urea and creatinine concentration compared with other groups [ 53 ]. Sharma and Singh [ 54 ] have recently reported that 24 h exposure to 10 and 150 mg/kg BW of Pb acetate induced increased in renal thiobarbituric acid reactive substances (TBARS) content that acts as an indicator of lipid peroxidation, as well as SOD and CAT activities in kidney of Balb-c mice.…”
Section: Introductionmentioning
confidence: 99%